Colostrum silage: fermentative, microbiological and nutritional dynamics of colostrum fermented under anaerobic conditions at different temperatures - doi: 10.4025/actascianimsci.v35i4.19870 - Ferreira, Lucas Silveira; Silva, Jackeline Thais; Paula, Marília Ribeiro de; Soares, Marcelo Cesar; Bittar, Carla Maris Machado (Acta Scientiarum. Animal Sciences, 2013)
The fermentative, microbiological and nutritional dynamics of bovine colostrum fermented under anaerobic conditions at different temperatures is provided. Colostrum was homogenized and stored in PET bottles in anaerobic conditions and incubated at controlled temperature (32.5 ± 1°C or 22.5 ± 1°C) or at room temperature (17.4 - 21.5ºC) and opened after 0, 1, 7, 14, 21, 28 and 35 days to determine fermentative and nutritional parameters and bacteria, yeast and mold counts. Further, pH rates showed significant variations during the fermentation period (p < 0.0001), with colostrum stored at 32.5°C, exhibiting the lowest rates and significant reduction during the first days. Titratable acidity and lactic acid concentration showed increasing rates and LAB development was intense, especially at high temperatures. After 35 days, about 50% of total nitrogen became non-protein N and casein fraction was reduced to 0.66% of total nitrogen. Lactose decreased during fermentation and fat concentrations were not affected by temperature. Results suggested that the temperature at which the colostrum was fermented directly influenced the speed and intensity of microbial population development and degradation of the main nutritional parameters, such as casein and lactose